HUBUNGAN KELELAHAN KERJA DENGAN KINERJA PERAWAT DI BANGSAL RAWAT INAP RUMAH SAKIT ISLAM FATIMAH KABUPATEN CILACAP - Kurniawati, Dian; Solikhah, . (Universitas Ahmad Dahlan, 2012)
Background: human reseources needed in hospitals provide care to the patient, the nurse workforce. The nurse was human resources that occupy the top in terms of the number of order thoughout the hospital. One the problems in worked on each worker that was exhausted. Problems in work can effect the level of performance of a worker. With the performance assessment we can know the performance levels that are generated on each worker in the work. Methods: this study used methods of observastional analytic cross-sectional approach with cross. Technique sampling used totally sampling, the sampling as a whole to serve as responder research. Data obtaind from the questionnaire the conducted analysis of chi-square with a 95% level of value (p<0,05). Results: based on results of research is the relationship between the fatigue of work performance wiyh the result 0,038 or value p the Ho<0.05 Ha was rejected and accepted, than there is a significant relationship between the fatigue of work performance. Magnitude of the relationship of two variables is 2,26%. Relationship between the fatigue of work with high performance was not good, but on a very meaningful work fatigue experienced low relationship that is less meaningful because, get results with low fatigue performance are not good. The level of errors in the generate 1,441. Conclucions: (a) there was a significant relationship between the fatigue performances of working with nurses in the inpatient ward. (b) A high work fatigue more dominant has a relationship to the performance of the nurse. Keyword: job burnout, performance, Nurses